TANGGUNGJAWAB BADAN PERTANAHAN NASIONAL (BPN) DALAM KEGIATAN PENGUKURAN DAN PEMETAAN BIDANG TANAH DALAM RANGKA PENERBITAN SERTIPIKAT MENURUT PP NO. 24 TAHUN 1997 DAN PMA/KBPN NO. 3 TAHUN 1997 (CONTOH KASUS PUTUSAN PENGADILAN NEGERI JAKARTA BARAT NOMOR 720/Pdt.G/2019/PN.Jkt.Brt.) - Susanto Agata Margita (Jurnal Hukum Adigama, 2021)
This article is entitled “Responsibility of the National Land Agency (BPN) in the Activities of Measurement and Mapping of Land Fields in the Context of Issuing Certificates according to Government Regulation No. 24/1997 and PMA/KBPN No. 3 of 1997 (Example Case of West Jakarta District Court Decision Number 720/Pdt.G/2019/PN.Jkt.Brt.)". To know the responsibilities of BPN and legal remedies in land measurement and mapping activities in the event of a dispute. Issuance of certificates carried out by BPN must comply with the requirements stipulated in the law. In the core there is a dispute between the parties against the same object. In this type of research, the approach is normative, namely by legislation with secondary data, namely articles, legal journals. What is the responsibility of BPN in land measurement and mapping activities? What are the legal remedies for landowners against certificates issued by BPN? negligence and carelessness in issuing certificates can cause problems. These problems can be detrimental to either party of the measurement and mapping. Legal efforts that can be taken to resolve the problem in 2 (two) ways, which can be resolved outside the court or can be resolved through the court.